The Discussion of Language and Poetry in A.R. Ammons's Garbage (Journal of the College of Languages (JCL), 2022)
A.R. Ammons's Garbage is a unique poem in all measures, starting from the title to the subject matter of the poem. Though it discusses the ecological repercussion of waste management, the long poem is written to shed light on the correlation between language\poetry and garbage. The paper argues that in his examination of language\poetry and garbage as both reflectors of human life and experience, Ammons claims that redemption is possible through both language and garbage by scrutinizing human experience whether low or high, mundane or sacred. This paper tries to examine Ammons's efforts to use the farfetched metaphor of garbage to discuss language and poetry-writing.